Surgical Treatment of Cubital Tunnel in Pediatric Athletes - Quinn, Daniel P.; Gu, Alex; Greenberg, Jeffrey A.; Fischer, Thomas J.; Merrell, Gregory A. (Journal of Hand and Microsurgery, 2018)
Background Cubital tunnel syndrome is the second most common upper extremity peripheral nerve entrapment syndrome. In particular, cubital tunnel has been documented occasionally in young, throwing athletes.Materials and Methods Billing databases were searched for patients undergoing surgical decompression of the ulnar nerve at the elbow, who were age 18 or younger at the time of surgery. Charts were reviewed and patients were included if they had an isolated mononeuropathy consistent with cubital tunnel syndrome and were symptomatic. Data on age of onset, duration of symptoms, Dellon classification, nerve subluxation, provocative testing results, nerve conductions, and exacerbating activities were abstracted. Patients were contacted for a postsurgical follow-up questionnaire.Results Seven patients were identified. The average age was 16, and duration of symptoms was 7 months. All seven patients had normal electrodiagnostic studies and had failed a course of conservative treatment. All were satisfied with surgery and felt improvement. One stopped playing their sport, and three had mild symptoms with varied activities.Conclusion Although uncommon, pediatric cubital tunnel syndrome does occur. Surgical release improves symptoms and return to activities. Nevertheless, some degree of symptoms often persists. Electrodiagnostic studies may be negative in many patients with an otherwise consistent history and examination.Level of Evidence This is a level IV therapeutic study.
Keywords: cubital tunnel syndrome; electrodiagnostic finding; Michigan Hand Questionnaire; pediatric athletes